The Research of Literary Criticism (Materialism in The Great Gatsby Novel by Fitzgerald) - Rohaniyah, Jaftiyatur (WACANA DIDAKTIKA, 2016)
The material as the lifeâs necessities of human changes into prestige of the humanÂ himself. Material is no longer interpreted as the lifeâs necessities but it changesÂ into money. It becomes the symbol of success and happiness. This shift process certainlyÂ brings a lot of change to the human nature. Material which at the beginning is consideredÂ as the life necessities turns into human obsession to reach the happiness. In the literaryÂ criticism, materialism is one of approach to analyze the values in the literary works. ItsÂ used by Fitzgerald to view the complexity of the story in the âGreat Gatsbyâ Novel, butÂ unfortunately the fact, its ironic because material satisfaction is only empty happiness asÂ reflected in this paper.